Peendorsement Akun Instagram @TasyaFarasya Terhadap Minat Beli Pengikutnya - Frisca Amelia Indrawan; Riesta Ayu Oktarina; Jokhanan Kristiyono (LPPM Stikosa-AWS, 2022)
The internet makes it easier for people to access information anytime and anywhere. Likewise with marketing trends, currently marketing has penetrated into digital marketing, where marketing can be done easily using social media or digital media. Through social media, business people can attract consumers with creative content. one of them is the beauty endorser or influencer method, these influencers create endorsement content for certain products to attract consumer buying interest. This study aims to see how the effect of endorsement of the Instagram account @tasyafarasya on interest in buying beauty products. This data collection technique is distributing questionnaires using google form to 100 respondents, namely followers and the method used is descriptive quantitative. The result of this study is that there is a significant effect of endorsement of the Instagram account @TasyaFarasya on the buying interest of followers, as evidenced by the linear regression results, the value of sig 0.00 < 0.05, which means that the variable X endorsement of the Instagram account @TasyaFarasya has a significant influence on the Y variable, the buying interest of followers. with a tendency of influence of 34.7%, both have a strong correlation of 0.645 and a coefficient of determination of 54.8%. These results mean that endorsements on Instagram play an important role in business through the communication process with followers or followers so that followers have an interest in buying beauty products.